2017
DOI: 10.1039/c7ra04432a
|View full text |Cite
|
Sign up to set email alerts
|

Rigid NON-donor pincer ligand complexes of lutetium and lanthanum: synthesis and hydroamination catalysis

Abstract: A rigid NON-donor pincer ligand was employed for the synthesis of neutral lutetium and anionic lanthanum alkyl complexes; the former is highly active for both intra- and inter-molecular hydroamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 41 publications
2
8
0
Order By: Relevance
“…The [Li­(THF) 4 ] 1+ cations in 1-La and 1-Ce have Li–O bond distances ranging from 1.900(4) to 1.953(4) Å (Table S1). These are in the range of previously reported structures of salts containing the [Li­(THF) 4 ] 1+ cation. …”
Section: Resultssupporting
confidence: 79%
“…The [Li­(THF) 4 ] 1+ cations in 1-La and 1-Ce have Li–O bond distances ranging from 1.900(4) to 1.953(4) Å (Table S1). These are in the range of previously reported structures of salts containing the [Li­(THF) 4 ] 1+ cation. …”
Section: Resultssupporting
confidence: 79%
“…X-ray quality crystals of 1 were grown from a concentrated O­(SiMe 3 ) 2 solution cooled to −30 °C (Figure ), and the solid state structure confirmed that zirconium is 5-coordinate with a distorted square pyramid geometry in which the XN 2 ligand donors and one dimethylamido group {N(3)} occupy basal positions and the second dimethylamido group {N(4)} occupies the axial position. This arrangement of the monodentate ligands mirrors that in structurally related [(XN 2 )­Ln­(CH 2 SiMe 3 )­(THF)] (Ln = Lu and Y), [Li­(THF) 4 ]­[(XN 2 )­La­(CH 2 SiMe 3 ) 2 ], and [(XA 2 )­An­(CH 2 –SiMe 3 ) 2 ] {An = Th and U; XA 2 = 4,5-bis­(2,6-diisopropyl-anilino)-2,7-di- tert -butyl-9,9-dimethyl-xanthene} , and is favored so as to allow the N -aryl groups to rotate away from the apical dimethylamido ligand to minimize unfavorable steric interactions. Consequently, the distance between the isopropyl C HMe 2 carbon atoms flanking the top of the square pyramid in 1 {C(33)···C(45) = 7.46 Å} is significantly greater than that below the base of the square pyramid {C(30)···C(48) = 5.03 Å}.…”
Section: Resultssupporting
confidence: 61%
“…The complexes discussed above highlight a greater tendency toward arene solvent coordination in more sterically open cationic alkyl species, especially monocyclopentadienyl complexes, and complexes of certain noncyclopentadienyl ligand systems. We have previously reported a range of actinide and rare earth alkyl complexes supported by 4,5-bis­(anilido)­xanthene pincer ligands, including complexes of Th, ,, U, Y, Lu, and La . Herein, we report attachment of a rigid, dianionic 4,5-bis­(anilido)­xanthene pincer ligand (XN 2 ) to zirconium by amine elimination, conversion of the resulting bis­(dimethylamido) complex to a dimethyl complex, and subsequent reactions with B­(C 6 F 5 ) 3 and [CPh 3 ]­[B­(C 6 F 5 ) 4 ] to afford a contact ion pair and arene-solvent-separated ion pairs, respectively.…”
Section: Introductionmentioning
confidence: 95%
“…IAHA of aminoalkenes catalyzed by rare-earth metal complexes has attracted most of attention. It has been demonstrated that organolanthanides are highly efficient and selective catalysts for the IAHA of various C–C unsaturations such as aminoalkenes, aminoalkynes, aminoallenes, and aminodienes. A probable stepwise σ-insertive mechanism (Scheme A) that comprises a turnover-limiting insertion of a C–C multiple bond into the Ln–N bond linked to rapid aminolysis of the resulting Ln–C bond was proposed on the basis of the following observations: (1) the increased ionic radius and improved coordination sphere result in increasing turnover frequencies (TOFs) common in lanthanide-catalyzed olefin transformations, suggesting that TOF is sensitive to olefin insertion; (2) the kinetic study revealed the rate to be first order in organolanthanides and zero order in aminoalkenes, arguing that the influence of aminolysis on the whole process is trivial. While in some cases, a distinctive aminoalkene-dependent first-order kinetic profile was observed even up to high conversions.…”
Section: Introductionmentioning
confidence: 99%